Theoretical Aspects of Creating Digital Twins of Transport Facilities - Shihnazarov J. A.; Ismatullaev A. F. (Scientific Trends, 2024)
Digital twins of transport facilities are virtual models of real vehicles, infrastructure and systems that are used to analyze, optimize and manage their operation. The article discusses key aspects of the use of digital twins in the transport sector, including their creation, integration and machine learning algorithms. Description of monitoring, diagnostics and forecasting methods using digital twins allows to improve the maintenance and operation of transport facilities, increase safety, reduce costs and increase environmental sustainability. Prospects for the use of digital twins in various transport segments, such as road, rail and air transport, as well as in urban transport systems, considering examples of successful implementations and future technologies.
Keywords: Digital twin, transport object, terminal, method , bottlenecks , optimization, software AnyLogic , Unity , 3dsmax.